Instalasi Digester dan Pelatihan Pembuatan Biogas dari Kotoran Sapi Untuk Bahan Bakar Industri dan Rumah Tangga - Rudianto, Rudianto; Zulhamidi, Zulhamidi; Pharmayeni, Pharmayeni; Ekawati, Irna; Putri, Gustiarini Rika (Journal of Industrial Community Empowerment, 2022)
Renewable energy has become much discussed issue today. One form of renewable energy that has not been managed optimally is biogas. Biogas can be produced from cow dung as a livestock waste. Currently the number of cattle in Nagari Lasi has reached around 1000 heads, large quantities for the biogas raw materials produced. The lecturers of the Department of Agro-Industrial Engineering of Polytechnic ATI Padang and CV. Kejulasi build a digester which is a device that produce biogas from cow dung. This biogas can be used as a fuel. The by-product of this process is compost that can be used for agriculture. 50 liters of cow dung, can produces biogas which can fully fill a 500 liters capacity package in three hours. And that amount of gas can be used for burning in the stove for two hours continuously that able to boil three liters water in about ten minutes.